An analysis of the impact of Covid-19 pandemic on the recruitment and selection practices & talent acquisition of Bangladesh Japan IT (BJIT) Limited - Anjum, Afra (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.